2022
DOI: 10.15562/bmj.v11i3.3395
|View full text |Cite
|
Sign up to set email alerts
|

Association between cartilage biomarker level and functional outcome in knee osteoarthritis patients receiving dextrose prolotherapy: a cross-sectional study

Abstract: Background: Knee osteoarthritis (KOA) is a degenerative joint disease with relatively high prevalence globally and is one of the leading causes of disability in the elderly population. Dextrose prolotherapy (DPT) has been proven effective in improving functional outcomes in knee osteoarthritis. The effect of hypertonic dextrose on cartilage biomarkers has not been evaluated. Purpose: To evaluate the association between a cartilage biomarker and changes in clinical outcomes among patients with KOA who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…It is in line with a previous study that showed significant improvement in NRS score, WOMAC total score, and all subscale scores of WOMAC after 12 weeks of follow-up dextrose prolotherapy injection. 24,25 This finding is similar to a previous report of significantly greater WOMAC score improvement after 18 weeks follow-up with dextrose prolotherapy injection, and was maintained through 52 weeks. [26][27][28] However, none of the previous studies compared the effectiveness of prolotherapy between mild and moderatesevere knee OA.…”
Section: Discussionsupporting
confidence: 90%
“…It is in line with a previous study that showed significant improvement in NRS score, WOMAC total score, and all subscale scores of WOMAC after 12 weeks of follow-up dextrose prolotherapy injection. 24,25 This finding is similar to a previous report of significantly greater WOMAC score improvement after 18 weeks follow-up with dextrose prolotherapy injection, and was maintained through 52 weeks. [26][27][28] However, none of the previous studies compared the effectiveness of prolotherapy between mild and moderatesevere knee OA.…”
Section: Discussionsupporting
confidence: 90%
“…This information is useful for researchers who want to understand the inflammatory reactions linked to each approach. [12][13][14] Biochemical markers IL-1 levels in the MIA group were significantly higher than in the control group (87.18 ± 15.8 ng/mL, 18.35 ± 6.79 ng/mL, respectively, p < 0.05). IL-1 was observed to be higher in the CFA group compared to the control group (113.75 ± 7.03 ng/mL, p<0.05).…”
Section: Knee-bends Scorementioning
confidence: 90%